Dampak Modal Intelektual dan Remunerasi Terhadap Kinerja Perusahaan dengan Kinerja Karyawan Sebagai Variabel Mediasi - Maulidya Dwi Mayreta; Suwandi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study investigates the relationship between intellectual capital and salary and corporate performance using employee performance as a mediating variable. The study's subjects are employees of start-up companies in Indonesia, who are emblematic of the dynamics and challenges of the modern workplace. This study uses a quantitative technique and an explanatory research design. This approach was chosen because it explains the causal relationship between independent variables (intellectual capital and compensation), mediating variables (employee performance), and dependent variables (business performance) using quantitative data that has undergone statistical processing. The research population consists of workers from Indonesian start-up companies. Purposive sampling is used in the sample determination process, and 100 respondents will be used as the research sample for this study. The results show that in order to close the gap between pay, intellectual capital, and corporate performance, employee performance is essential. As a result, it is advised that companies concentrate more on controlling their intellectual property by improving employee skills and abilities and establishing a system of fair and competitive pay.